A Case Report on Kasabach Merrit Syndrome (Bangladesh Journal of Child Health, 2012)
Kasabach Merritt syndrome (KMS) is an uncommon complication of large haemangioma in which there is thrombocytopenia and coagulopathy. We report a case of a new born male baby presented with a large haemangioma on the right upper extremity and his initial laboratory tests were consistent with consumptive coagulopathy. He was diagnosed as a case of KMS and treated with oral prednisolone. DOI: http://dx.doi.org/10.3329/bjch.v36i2.13091 Bangladesh J Child Health 2012; Vol 36 (2): 105-107